Methodologies for Patellid Limpets’ Aquaculture: From Broodstock Management to Juveniles - Castejón, Diego; García, Loreto; Cañizares, José M.; De Girolamo, Mirko; Nunes, Carla; Isidro, Eduardo; Courtois de Viçose, Gercende; Nogueira, Natacha; Andrade, Carlos A. P. (Frontiers in Marine Science, 2022)
The production of cultured limpets is a recent research field contributing to aquaculture diversification, focusing on low trophic species, while reducing carbon footprint. Limpets are gastropods that colonize rocky substrates, mostly present on tidal and subtidal shores. This animal group is highly demanded commercially and yet endangered in several regions. The aquaculture production of limpets has been traditionally challenging. The most successful reproduction method has been the gonadal dissection, as artificial spawning induction showed a limited success up to date. Moreover, methods for larval culture, settlement, and juveniles grow-out have been poorly developed and remain largely unknown. In the last years, advances in this field are leading to the optimization of methods to enhance larval production, larval culture, settlement induction of competent larvae, and management of post-larvae and juveniles. The present manuscript reviews these advances, obtained within the framework of AQUAINVERT project, focusing on broodstock management, gametes release, larval production, larviculture, settlement and grow-out of post-larvae, and providing an update on the actual state of the art in limpets’ aquaculture.